EFEKTIFITAS MATERI AQIDAH AKHLAK DALAM MENINGKATKAN KECERDASAN SPIRITUAL DAN EMOSIONAL SISWA - Sa'adatul Abadiyah; Ulil Hidayah (LPPM STAI Muhammadiyah Probolinggo, 2024)
One of the ways that the ideal of life is realized is through education, especially Islamic education among Muslims, which serves to internalize these Islamic principles and pass them on to the next generation. Schools as educational institutions have an important role in implementing the learning objectives of moral beliefs. Because, developing spiritual and emotional intelligence in students has a significant impact in shaping character. This research is of descriptive qualitative type to analyze material on moral beliefs in increasing the spiritual and emotional intelligence of students at Madrasah Tsanawiyah Miftahul Ulum Probolinggo. Based on the results of the study, MTs Miftahul Ulum Anak Probolinggo has strong emotional intelligence. They are able to regulate their emotions effectively, as seen by the fact that they do not feel intimidated by the rules and regulations that exist in school. Meanwhile, it can be said that the students of MTs Miftahul Ulum Probolinggo often have good spiritual intelligence in terms of their strong faith and acute environmental sensitivity.